ANALISIS TREN PERKEMBANGAN KINERJA INVESTASI ASING MENURUT BIDANG USAHA SEBELUM DAN SESUDAH PANDEMI COVID 19 DI JAWA TIMUR - sutarmin; Sugiyanto; Dra. Wiwik Budiarti, MM (Develop, 2022)
This study aims to analyze the trend of investment performance development based on the business sector before and after the covid 19 pandemic. The analysis is carried out by comparing the rate of movement of foreign investment for the period 2016 to 2021 based on the business fields carried out in East Java. Data is collected through documentation, then data display is carried out, namely compiling data, then simplification is carried out according to data needs; the next step is to present the data in the form of images, then interpret the comparative data and the last step is to formulate conclusions and provide recommendations.The performance of foreign investment in 2016 in East Java on national performance contributed IDR26.57 trillion from IDR396.64 trillion or 6.70%. In 2017, East Java's performance towards foreign investment nationally contributed IDR20.93 trillion from IDR430.46 trillion or 4.86%. In 2018 it decreased compared to the previous year, East Java's foreign investment performance nationally contributed IDR17.87 trillion from IDR392.73 trillion or 4.55%. In 2019 it decreased compared to the previous year, East Java's 2019 foreign investment performance nationally contributed IDR12.99 trillion from IDR4223.13 trillion or 3.07%. However, starting in 2020, East Java's foreign investment performance has increased nationally, contributing IDR 22.69 trillion from IDR 412.79 trillion or 5.50%. And in 2021 there will also be an increase in the investment value of IDR 27.00 trillion from IDR 453.96 trillion or 5.95%. So it can be concluded that from the results of the analysis, in 2019, 2020 and 2021, East Java's contribution during the COVID-19 period actually showed a significant increase.